Application of Local Community Wisdom in Rehabilitation of River Erosion in Kampar District - Saiful Adli bin Suhadak; Arrahmah Dea Syamsaputri; Rosdianto; Syafri Anwar (Sumatra Journal of Disaster, Geography and Geography Education, 2025)
Research on applying local wisdom in rehabilitating river erosion was carried out in the Kenegarian Rumbio Kampar District. The aim of this research is to identify efforts to rehabilitate river erosion, identify factors that are inhibiting in rehabilitating river erosion, identifying factors that are inhibiting in rehabilitating river erosion, as well identifying and evaluating efforts made in overcoming the obstacles of river erosion rehabilitation at Kenagerian Rumbio Kabupaten Kampar. Results of research local wisdom are obtained 1) effort rehabilitation of river erosion has been good because it has been run down hereditary by the community, 2) factors resistor there are 4, the hat is household waste dumped into the river, replacement plants of river cliff, mining activities, and land clearing In river banks, and 3) efforts undertaken to overcome the obstacles of river erosion rehabilitation done in 2 ways that are by the method of vegetative and method of civil engineering